Pedagogical practice in the formation of professional skills of future teachers - results of research - Minchanovska Oleksandra; Khruzd-Matushchyk Alisa (Borys Grinchenko Kyiv Metropolitan University, 2016)
Ensuring the right to children education, youth and later adults has always been one of the main responsibilities of each society. Modern transformations occurring in society and education system reform in our country, raising the question of a new model for training of teachers - educators. Training of teachers - educators carried out according to curricula that include theoretical and practical units. Theory and practice are interconnected source of knowledge required in the training of future teachers. The subject of study of this article is to educate students of pedagogy with emphasis on important pedagogical practices in preparation for the profession. The article consists of several parts. In the first part we characterize the role of pedagogical practices in shaping the skills of future teachers, and describe the scope of educational activities for teachers. The second part is a presentation fragment copyright conducted research among students of pedagogical specialties. The article ends with conclusions.